2015
DOI: 10.1016/j.cbpa.2014.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Using non-enzymatic chemistry to influence microbial metabolism

Abstract: The structural manipulation of small molecule metabolites occurs in all organisms and plays a fundamental role in essentially all biological processes. Despite an increasing interest in developing new, non-enzymatic chemical reactions capable of functioning in the presence of living organisms, the ability of such transformations to interface with cellular metabolism and influence biological function is a comparatively underexplored area of research. This review will discuss efforts to combine non-enzymatic che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…While the former skillfully employ synthetic catalysts and reagents to build up complex molecules, the latter harness the reactivity of biocatalysts in living organisms to produce compounds from fermentation . Although these approaches have been traditionally considered to be incompatible, small‐molecule catalysts that can interface with cellular metabolism have the potential to expand biological function without the need for genetic manipulation . For example, such biocompatible catalysts could be part of cellular factories, in which they perform new‐to‐nature transformations to diversify molecules produced by an organism .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…While the former skillfully employ synthetic catalysts and reagents to build up complex molecules, the latter harness the reactivity of biocatalysts in living organisms to produce compounds from fermentation . Although these approaches have been traditionally considered to be incompatible, small‐molecule catalysts that can interface with cellular metabolism have the potential to expand biological function without the need for genetic manipulation . For example, such biocompatible catalysts could be part of cellular factories, in which they perform new‐to‐nature transformations to diversify molecules produced by an organism .…”
Section: Figurementioning
confidence: 99%
“…[2,3] Although these approaches have been traditionally considered to be incompatible, small-molecule catalysts that can interface with cellular metabolism have the potentialt oe xpand biological function without the need for genetic manipulation. [4][5][6] For example,s uch biocompatible catalysts could be parto fc ellular factories,i nw hich they perform new-to-nature transformations to diversify molecules producedby an organism. [7][8][9][10] Thus, such ac oncertede ffort of synthetic chemistry and metabolic engineering could pave the way toward the direct synthesis of value-added compounds in cellular settings.A dditionally,b iocompatible catalysis holds promise for biomedical applications, such as targeted drug release/synthesis, [11][12][13][14][15] the disruption of cell-cellc ommunication or rescuing dysfunctional enzymes involvedi nh uman diseases.…”
mentioning
confidence: 99%
“…83,87 While it has been established that these processes are important in regulating key events in the biofilm life cycle, the exact mechanism governing detachment and dispersal events are complex and still poorly understood. 105,106 Regardless of how the specific detachment cues are detected, the phenotypic changes they initiate are evident. Induction of a cascade of signalling pathways may result in an increase in matrix-degrading enzymes, a decrease in EPS 107 and the evacuation of the interior of microcolonies, forming hollow vacuoles ( Figure 2), which release and disperse planktonic bacteria into the environment to form new colonies on a distal, nutrient-rich surface.…”
Section: 100mentioning
confidence: 99%
“…83,87 While it is well established that these processes are important in regulating key events in the biofilm lifecycle, the intricate details of how they work are still not well understood. 105,106 In an attempt to discover the function of free radicals and the role of oxidative stress in biofilm formation and dispersal, Barzegar Amiri Olia et al, developed a novel profluorescent nitroxide (45) that detects free radical and redox processes associated with oxidative stress during P. aeruginosa biofilm growth (Figure 18). 349 Confocal laser-scanning microscopy and subsequent co-localization studies using digital image analysis revealed that conditions of oxidative stress occur predominantly in the EPS and in live cells during normal biofilm growth.…”
Section: 287mentioning
confidence: 99%
“…The valuable natural product 9 -tetrahydrocannabinol (THC) is one of those compounds for which chemical synthesis might benefit from the introduction of biocatalytic steps (Wallace et al, 2015). In Nature, THC is exclusively found in the plant Cannabis sativa L., which has a long history in medicinal use, driven by the increasing interest in the last decades in the treatment of e.g., multiple sclerosis and spasticity (Goodin, 2004).…”
Section: Introductionmentioning
confidence: 99%